BIOLOGICAL CYCLE AND MORPHOLOGICAL CHARACTERIZATION OF THE DEVELOPMENTAL STATES OF Tuthillia cognata (HEMIPTERA: PSYLLIDAE) IN CAMU CAMU - CAMPOS-CELESTINO, Vilma Erica (2023)
The jumping louse, Tuthillia cognata (Hemiptera: Psyllidae) is a pest that causes severe deformations in the leaf buds of Myrciaria dubia (camu camu) in the Peruvian Amazon, therefore, a study was carried out with the objective of determining the morphological characteristics of each stage of development, the duration and longevity of T. cognata adults in young shoots of camu camu. The research was carried out under laboratory conditions (temperature: 26,9 ± 2°C, relative humidity: 6,6 ± 5% and 12:12 h Light: Dark) in Pucallpa, Peru. Morphological characteristics of each stage of development, duration and longevity of T. cognata adults in young shoots of camu camu were determined. The duration from egg to adult was 17,8 ± 0,6 (12 to 23) days and longevity for females was 38,6 ± 1,3 (37 to 40) days and for males 35,6 ± 1,5 (34 to 38) days.